Pengaruh Brand Awareness, Perceived Quality dan Brand Loyalty Terhadap Keputusan Pembelian Le Mineral di Kota Batam - Rina Susanti; Hikmah (Pusat Riset dan Inovasi Nasional, 2026)
The increasingly intense competition in the bottled water industry encourages every manufacturer to not only offer good product quality, but also strengthen brand awareness and build consumer loyalty. This study aims to analyze the influence of brand awareness, perceived quality, and brand loyalty on purchasing decisions for Le Minerale products in Batam City. The research method used is a quantitative approach with a descriptive nature, designed to measure and explain the causal relationship between variables objectively and measurably. The population in this study were consumers who have purchased and consumed Le Minerale products in Batam City, with an unknown population size. The determination of the number of samples was carried out using the Jacob Cohen formula, resulting in 204 respondents, selected through a purposive sampling technique based on product purchasing experience criteria. Data collection was carried out by distributing questionnaires, then analyzed through validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the partial test indicate that brand awareness has a positive and significant effect on purchasing decisions. Perceived quality is also proven to have a positive and significant effect on purchasing decisions. In addition, brand loyalty partially has a positive and significant effect on purchasing decisions for Le Minerale products. Simultaneous testing shows that brand awareness, perceived quality, and brand loyalty collectively have a positive and significant influence on purchasing decisions at Le Minerale in Batam City